Response of Gumuz Sheep to Alternative Supplement Feed Ingredients, Ethiopia - Alemu Tarekegn; Yeshambel Mekuriaw; Firew Tegegne (Scientific Papers Animal Science and Biotechnologies, 2023)
An experiment was conducted using twenty four Gumuz ram lambs with an initial body weight of 19.05±2.29 kg (mean±SD) to investigate the response to supplementations on feed intake, body weigh change and carcass characteristics of Gumuz sheep. The sheep were treated against endo- and ecto- parasites before commencing the study. The experimental design was a Randomized Complete Block Design (RCBD) with six replications. The treatments were: natural pasture hay alone (T1), natural pasture hay+ 1noug seed cake (NSC):1 wheat bran (WB) (T2), natural pasture hay + 2NSC: 1WB (T3) and natural pasture hay + 3NSC:1WB (T4). The supplements were offered at the rate of 400 g/day, which were offered twice per day at 8 a.m. and 4 p.m hours in equal portions. The feeding trial was carried out for 90 days after 15 days of adaptation period to the experimental feeds and conditions, which were then followed by carcass evaluation at the end of the study. Supplemented treatments had higher (P<0. 01) total DMI (712.53-724.92 g/d) than the control (672.55 g/d). Supplemented sheep gained BW within the range of 44.26-86.67g/sheep/day with significantly higher (p<0.001) differences among the supplemented groups. Better (p<0.001) FCE was observed in the supplemented treatments than the control, but no significant differences (p>0.001) were recorded among the supplemented treatments. Sheep fed natural pasture hay alone had the lowest net return (-114.46 ETB) and had lowest (p<0.001) values for carcass parameters than the supplemented treatments. The possible reason might be because of the relatively less body condition which could not attract prime price in the market. The highest (p<0.01) dressing percentage (44.22%) as a proportion of slaughter weight was recorded in T4. Supplemented treatments had rib-eye muscle area in a range of 6.37-10.12 cm2 and the lowest rib-eye muscle area (4.71cm2) was recorded in the control treatment. Sheep supplemented with 3NSC:1WB (T4) had the highest net return (287.78 ETB and highest MRR (4.96) compared to the other supplemented treatments. Thus, it is recommended that supplementation of hay with 400 g/head/day concentrate mixture at 3NSC:1WB proportion is biologically efficient and potentially profitable in the feeding of growing Gumuz sheep.